Peningkatan Akses Layanan Keuangan pada Masyarakat Unbanked di Indonesia melalui Financial Technology - Qiyqiy Fithri Awamirillah; Shinta Maharani (Journal of Economics, Law, and Humanities, 2022)
Financial Technology (Fintech) is defined as financial services integration and solutions based on technology. Unbanked is a group of people who do not have savings in the bank. There is a substantial potential increase in financial services for the unbanked by utilizing Fintech in Indonesia. It is seen from the young population and the high growth of internet access. However, compared to other countries, the development of Fintech access in Indonesia is still far behind. The theory used in this research is the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2). The data were analyzed using the path analysis method using the bright partial least square (Smart-PLS) software. Respondents in this study amounted to 304 people from all over Indonesia. The variable constructs used in this study are usefulness, ease of access, preference, behavioral intention to use, and actual system use. The results of this study explain that usefulness has a significant positive effect on ease of access; help has a positive impact on behavioral intention to use, but the value is not substantial; ease of access has a positive effect on preference and has a considerable discount; priority harms behavioral intention to use, but the value is not significant; pick has a positive impact on actual system use, but the value is not the substantial and behavioral intention to use has a positive effect on actual system use, but the value is not significant.